2017
DOI: 10.1080/15289168.2016.1255499
|View full text |Cite
|
Sign up to set email alerts
|

The Adolescent Psychotherapy Q-Set (APQ): A Validation Study

Abstract: Objective: This article reports the validation of the Adolescent Psychotherapy Q-set (APQ), a newly developed instrument, adapted from the well-established Psychotherapy Q-Set (PQS) and the Child Psychotherapy Q-set (CPQ). The APQ aims to describe the psychotherapy process in the treatment of adolescents in a form suitable for quantitative comparison and analysis. Method: The validation was conducted with the ratings of seventy audio-recorded youth psychotherapy sessions from a range of therapists, patients, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 43 publications
(50 reference statements)
1
36
0
8
Order By: Relevance
“…This provides a way to characterise individual sessions of an adolescent therapy and its progress over time in clinical terms that are quantitatively analysable. It can also be used in different forms of treatments, and indeed Calderon's work showed that the APQ distinguished between the techniques of therapists conducting CBT versus psychoanalytic psychotherapy, and that these differences corresponded in predicted ways to the appropriate CPPS scales (Calderon, Schneider, Target, & Midgley, 2017). We therefore have a way in the future to relate content and technique in these sessions (which have been shown to be adherent to their manualized models) to the individual patients' outcomes.…”
Section: (6) Finally! Designing and Conducting A Major Randomized Conmentioning
confidence: 98%
“…This provides a way to characterise individual sessions of an adolescent therapy and its progress over time in clinical terms that are quantitatively analysable. It can also be used in different forms of treatments, and indeed Calderon's work showed that the APQ distinguished between the techniques of therapists conducting CBT versus psychoanalytic psychotherapy, and that these differences corresponded in predicted ways to the appropriate CPPS scales (Calderon, Schneider, Target, & Midgley, 2017). We therefore have a way in the future to relate content and technique in these sessions (which have been shown to be adherent to their manualized models) to the individual patients' outcomes.…”
Section: (6) Finally! Designing and Conducting A Major Randomized Conmentioning
confidence: 98%
“…The therapeutic process was examined using the Adolescent Psychotherapy Q-Set (APQ; Calderon et al, 2017). The APQ is an adaptation of the Psychotherapy Q-Set (PQS; Jones, 2000), used in adult process research, and the Child Psychotherapy Q-Set (CPQ; Schneider & Jones, 2004), used in child process research.…”
Section: Adolescent Psychotherapy Q-set (Apq)mentioning
confidence: 99%
“…The Q-set comprises 100 items that capture a wide range of phenomena (pantheoretical) and with Q-sort procedure the items are sorted into 9 piles from "least characteristic" to "most characteristic". The later development of The Child Psychotherapy Q-Set (CPQ) (Schneider, 2004) and Adolescent Psychotherapy Q-set (APQ) (Calderon, Schneider, Target, & Midgley, 2017) were adapted from the PPQ. The instrument enables description of the psychotherapy process in a form suitable for quantitative comparison and analysis.…”
Section: Instruments To Measure Processmentioning
confidence: 99%
“…APQ is intended to be neutral with respect to any particular theory of psychotherapy and should permit the portrayal of a wide range of events, interventions, and processes in the psychotherapy process. The validation of APQ was conducted with ratings of audio-recorded youth psychotherapy sessions from different therapeutic approaches (Short-Term Psychoanalytic Psychotherapy and Cognitive Behavioural Therapy) (Calderon et al, 2017).…”
Section: Predictors and Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation